The diabetes-related self-care activities of people with type 2 diabetes: their level and associated factors - Zhao, FangFang (fi=Turun yliopisto|en=University of Turku|, 2019)
The adherence to diabetes-related self-care activities (DRSCA) is not optimal, although studies about DRSCA have progressed much. Additional information about the factors associated with the level of DRSCA is necessary for supporting patients in diabetes management. This study aimed to examine the DRSCA of people with type 2 diabetes mellitus (T2DM) and associated factors. First, a systematic review with a meta-analysis was used to synthesize the effects of theory-based self-management education on DRSCA, which aimed to provide implications and clues for the second phase of the study. Second, an empirical study investigated background information and outcome information related to DRSCA. DRSCA were measured at two time points. The systematic review included 22 studies with 6,099 participants after selecting the included studies from five databases. The empirical study used the survey method two times, involving 251 participants with T2DM the first time, and 155 participants completed a valid questionnaire about DRSCA the second time. At the first time point, the information was collected as follows: the background information consisted of demographic information, health information, social support and optimism; the outcome information included negative feelings and positive health. The subsequent DRSCA, covering three months, were measured in order to test the association of social support and optimism with subsequent DRSCA. The systematic review indicated that theory-based self-management education had more effects on DRSCA than routine care, and this implied that it is necessary to encourage people with T2DM to actively perform DRSCA. The empirical study provided encouraging information with which patients with T2DM could improve DRSCA. The main findings showed that objective support, support utility and optimism were significantly and positively associated with the level of DRSCA. In addition, DRSCA were associated with reduced perceived stress (one component of negative feelings) but not with anxiety and fatigue after adjusting for covariates. DRSCA can improve one component of positive health but this is not significantly associated with resilience and DRQoL after controlling covariates. The study provides additional information to encourage patients to be more involved in DRSCA in order to improve their subjective well-being and to reduce perceived stress. In addition, the role of optimism in DRSCA was examined, and this may help to draw attention to its role in diabetes care.

Tyypin 2 diabetekseen liittyvät omahoitotoimenpiteet, niiden taso ja niihin liittyvät tekijät Hoitoon ei aina sitouduta parhaalla mahdollisella tavalla, vaikka tutkimusnäyttö diabeteksen omahoidosta (diabetes-related self-care activities, DRSCA) on vahvistunut. Lisätietoa omahoitoon liittyvistä tekijöistä tarvitaan tukemaan potilaita diabeteksen hoidossa. Tämän tutkimuksen tarkoituksena oli analysoida tyypin 2 diabetesta sairastavien henkilöiden omahoitoon liittyviä tekijöitä. Ensiksi, systemaattista katsausta ja meta-analyysiä käytettiin muodostamaan käsitys teoriapohjaisen omahoito-opetuksen vaikutuksista omahoitotoimenpiteisiin, ja perustakse empiiriselle tutkimusvaiheelle. Toiseksi, empiirisellä tutkimuksella analysoitiin omahoitotoimenpiteiden taustatekijöitä ja hoitotuloksia. Omahoitotoimenpiteitä mitattiin kahdessa aikapisteessä. Systemaattisessa katsauksessa valittiin viidestä tietokannasta 22 tutkimusta, joissa oli yhteensä 6,099 tutkimushenkilöä. Empiirinen tutkimus koostui kyselyistä kahdessa aikapisteessä, joista ensimmäisessä 251 ja toisessa 155 tyypin 2 diabeetikkoa palautti omahoitoon ja siihen liittyviin tekijöihin kohdistuvat kyselylomakkeet. Ensimmäinen lomake sisälsi potilaiden taustatietoja demografista tekijöistä, terveydestä sekä tietoja sosiaalisesta tuesta ja optimismista; hoitotuloksiin liittyen kerättiin myös tietoa kielteisistä tunteista ja myönteisistä terveysvaikutuksista. Toisessa aikapisteessä tuen ja optimismin vaikutusta diabeteksen omahoitotoimiin mitattiin 3 kuukauden kuluttua. Systemaattinen tarkastelu osoitti, että teoria-pohjainen omahoidon opettaminen vaikuttaa omahoitoon enemmän kuin rutiiniomainen opetus, ja että tyypin 2 diabeetikkoja tulisi motivoida ottamaan enemmän vastuuta hoidostaan. Empiirinen tutkimus toi esiin seikkoja, joiden perusteella voitaisiin kehittää omahoidon laatua. Sosiaalinen tuki, tuen hyväksyminen ja optimismi olivat merkitsevästi yhteydessä omahoidon tasoon. Omahoito liittyi matalampaan koetun stressin määrään, joka on yksi negatiivisten tunteiden komponenteista, mutta ei ahdistuneisuuteen tai väsymykseen, kun vakioivat tekijät huomioitiin. Omahoito voi parantaa koettua terveyttä ja hyvinvointia, joka on yksi hyvän terveyden komponenteista, vaikka tilastollista yhteyttä resilienssiin tai sairauteen liittyvään elämänlaatuun ei kyetty osittamaan. Tutkimus tuottaa lisätietoa siitä, miten yksilöitä voidaan rohkaista aktiivisempaan rooliin omahoidossaan subjektiivisen hyvinvoinnin parantamiseksi ja stressin vähentämiseksi. Lisäksi optimismin roolia omahoidossa tutkittiin, mikä saattaa auttaa optimismin merkityksen huomioimisessa diabeteksen hoidossa.